The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1159/000491465
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Pathway in Age-Related Neurological Disorders: Insights into MicroRNAs

Abstract: A general hallmark of neurological diseases is the loss of redox homeostasis that triggers oxidative damages to biomolecules compromising neuronal function. Under physiological conditions the steady-state concentrations of reactive oxygen species (ROS) and reactive nitrogen species (RNS) are finely regulated for proper cellular functions. Reduced surveillance of endogenous antioxidant defenses and/or increased ROS/RNS production leads to oxidative stress with consequent alteration of physiological processes. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 178 publications
(249 reference statements)
1
48
0
6
Order By: Relevance
“…miRNAs are involved in the regulation of intracellular redox and post-transcriptional regulation of key components of the ROS/ reactive nitrogen (RNS) pathway, including Nrf2. 9 Jing Zhou et al 10 showed that H 2 O 2 activated the Nrf2 signalling pathway in a mouse corneal epithelial progenitor cell line (TKE2) and increased the expression of miR-125b.…”
Section: Mir-125b Belongsmentioning
confidence: 99%
See 1 more Smart Citation
“…miRNAs are involved in the regulation of intracellular redox and post-transcriptional regulation of key components of the ROS/ reactive nitrogen (RNS) pathway, including Nrf2. 9 Jing Zhou et al 10 showed that H 2 O 2 activated the Nrf2 signalling pathway in a mouse corneal epithelial progenitor cell line (TKE2) and increased the expression of miR-125b.…”
Section: Mir-125b Belongsmentioning
confidence: 99%
“…Recent studies have shown that miRNAs regulate Nrf2 directly or indirectly, which may be an important mechanism underlying miRNAs involvement in cell differentiation and apoptosis. miRNAs are involved in the regulation of intracellular redox and post‐transcriptional regulation of key components of the ROS/reactive nitrogen (RNS) pathway, including Nrf2 . Jing Zhou et al showed that H 2 O 2 activated the Nrf2 signalling pathway in a mouse corneal epithelial progenitor cell line (TKE2) and increased the expression of miR‐125b.…”
Section: Introductionmentioning
confidence: 99%
“…Nrf2, involved in redox reactions, participates in ER stress-induced apoptosis and together with ATF4 repress miR-106b-25 cluster. It has been shown that the Nrf2/ATF4/miR-106b-25 cluster may be relevant for ALS pathogenesis [244]. In addition, miR-142-5p, that is downregulated in the CSF of ALS patients, has been shown to reduce OS via the upregulation of the Nrf2 signaling pathway [236,245].…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…In fact, the DNA damage from ionizing radiation has thus been attributed to the formation of radicals from the radiolysis of water molecules, as will be treated extensively in a later paragraph. More recently, also in light of the progress on understanding radicals as elements of intracellular and intercellular communication (Paladino et al, 2018), more and more weight is being given to biological pathways mediated by mitochondrial oxide-reduction while intermediate metabolic products can lead to oxidation, nitrosylation, and alkylation of DNA (Hekimi et al, 2011). Whatever their origin, ROS are able to induce DNA damage either directly or indirectly by interfering with the activity of the epigenetic regulatory factors and the DDR proteins.…”
Section: Aging: Definition and Characteristicsmentioning
confidence: 99%